Las comparaciones entre las ecuaciones de predicción de la tasa metabólica en reposo y la calorimetría indirecta en los adolescentes obesos - de Oliveira, Bruno A.P.; Nicoletti, Carolina F.; Gardim, Camila B. [UNESP]; de Andrade, Vitor L.; Freitas Júnior, Ismael F. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2014)
Objective: To measure the accuracy of predictive equations of resting metabolic rate (RMR) in obese teenagers in relation to indirect calorimetry (IC). Methods: This study was conducted with 116 obese teenagers (60 males; 13.7±1.1 years). The RMR was calculated from Harris and Benedict, Schofield, WHO, Henry and Rees equations. The RMR was measured by the QUARK-RMR system. The comparison between predictive equations and IC was by the Student’s t test. The reliability of data between predictive equations and IC was verified by the typical error of measurement (TEM) and the coefficient of variation (CV%). Results: Henry’s equation was significantly different from IC (p<0.02). The CV% found for each equations compared to IC turned was low. However, when the TEM was measured it was considered high in absolute values which can cause errors when estimating the RMR. Therefore, it is important that specific predictive equations are developed for Brazilian obese teenagers.
Comparisons between predictive equations of resting metabolic rate and indirect calorimetry in obese teenagers
Keywords: Indirect calorimetry; Obesity; Predictive equations; Resting metabolic rate; Teenagers